Preventing violence against women and girls: educational work with children and young people - Ellis, Jane (The Policy Press, 2014)
The need for children and young people to learn about violence against women and girls (VAWG) has been voiced since the late 1980`s. This is the first ever book on educational work to prevent VAWG, providing the most comprehensive contribution to our knowledge and understanding in this area. By bringing together international examples of research and practice, the book offers insight into the underpinning theoretical debates and key lessons for practice, addressing the complexities and challenges of developing, implementing and evaluating educational work to prevent VAWG. This multidisciplinary book will be of interest to educationalists, VAWG and child welfare practitioners, policy makers, researchers and students